Oral lesions in paediatric patients with COVID-19 and Paediatric Inflammatory Multisystem Syndrome: a review - Khaleda Zaheer; Roshni Sanikop; Aisling Cant; Nabina Bhujel; Rabindra P. Singh (Elsevier, 2022)
Paediatric patients comprise a small proportion of the SARS-CoV-2 infected population. They usually present with mild symptoms, however a small proportion of them may require intensive care due to shock and multi-organ failure related to Paediatric Inflammatory Multisystem Syndrome temporally associated with SARS-CoV-2 (PIMS-TS).This review article summarises the oral mucosal lesions in children with COVID-19 and PIMS-TS. The most common sites affected are the tongue and lips. Commonly reported lesions include cheilitis, dry and red lips, and tongue swelling. This article is of importance to all healthcare professionals involved in the multidisciplinary care for this group of patients.